EFEKTIVITAS MEDIA POWERPOINT INTERAKTIF SUB MATERI EKSKRESI GINJAL TERHADAP MOTIVASI SISWA SMPN 16 PONTIANAK - Banyu, Baras; Panjaitan, Ruqiah Ganda Putri; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to identifying the effect of interactive powerpoint media to the students learning motivation on kidney excretion sub material at eighth grade of SMP Negeri 16 Pontianak. This research form was experimental with one-shot case study design. The sampling technique used was random sampling, with VIII B class as the experimental class and VIII A class as the control class. The sample in this research amounted to 60 students consisting of 30 students from VIII B class and 30 students from VIII A class. The instrument research were validation sheet of interactive powerpoint media and learning motivational questionnaires. The validation sheet of interactive powerpoint media consists of 2 aspects namely content and language. While the learning motivational questionnaires consists of 6 aspects namely attraction, seriousness, interest, activeness, satisfaction, and optimism. The results of media validation indicate that the media is suitable for use. The questionnaires effect size value obtained is 0.2 with a low category, giving an effect of 7.93%. So, can be concluded that interactive powerpoint learning media is declared valid with an effect of 7.93% on students learning motivation.Â Keywords: Interactive Powerpoint, Kidney Excretion Sub Material, Students Learning Motivation